NEOTECTONIC DEFORMATION OF NORTH PARNIS - Χατούπης, Θ.; Φουντούλης, I. (Bulletin of the Geological Society of Greece, 2004)
The morphotectonic analysis in the eastern part of Biotic Asopos river catchment, results to an explicit picture of a new drainage network with individual abnormalities that are focused mainly in phenomena of "piracy" and abrupt knick points. Topographic sections along the main streams and correlation between rose diagrams of faults and stream network reveal an influence of the drainage network (E-W and N-S direction) from the active tectonic structure of E-W to WNW-ESE direction, which is accompanied by phenomena of intense depth erosion transversely to the main active tectonic faults. The important dextral slip component of the main active fault zones (Sfendali-Avlona and Milesi Oropos) has influenced the alpine tectonic structure, determining the current NE-SW spread of Upper Cretaceous limestones and changing the direction of flysch axes from NNE-SSW in mountainous Parnis area to ENE-WSW in the flat area of Malakasa. The distribution of planation surfaces in combination with the presence of en echelon oblique slip faults of WNW-ESE direction, reveal a complex kinematic evolution, with main characteristics the progressive rotation of tectonic blocks to the WNW for the mountainous south area and to the SSW for the NE area of low relief.